THE ROLE OF CONSUMER INVOLVEMENT ON INNOVATION AND NEW PRODUCT DEVELOPMENT PROCESS: META-ANALYSIS AND WORD CLOUD TEXT ANALYSIS - TURP GÖLBAŞI , Bilge (SSD Journal, 2022)
Today, businesses are trying to make the concept and process of innovation a collective phenomenon by collaborating in innovation activities and opening up, especially thanks to the cooperation and relationships they have established with consumers. In order for new economic paradigms to be superior, new paradigms must have factors that can be defined as a group of key inputs. From this point of view, there are many factors that affect the success and performance of innovation and new product development. Consumers have become the most important source of innovation. Studies show that the impact of consumer integration on innovative products and resource expenditure is enormous. In this study, the aforementioned paradigms were brought together and a literature review of the projects and researches in the field of innovation, consumer effects of new product development processes and innovation integration between the years 2005- 2022 was conducted. Then, the text data of these studies were brought together and translated and a dataset was created. Then, word cloud text analysis, which is a powerful visualization tool, was applied on the Anaconda-Pycharm software with python programming language to provide a statistical view. It has been observed that the results obtained by this text analysis method, the most frequent terms settle in the center by increasing their density, and the lower frequency terms are located towards the borders by decreasing. According to the results of the observation, it was found that the terms with high frequency were “NPD (New Product Development), consumer participation and innovation” and were clearly concentrated in the center. As a result, in parallel with the results of meta-analysis and word cloud text analysis, it is concluded that the innovation and new product development strategy is "consumer participation", that is, staying close to the consumer, so that the right users can provide the company with ideas that promote new products.In future studies, considering that product innovations have different dimensions as "technology innovation" and "market innovation", the factors that demand different levels of information from the consumer depending on the innovation level should be evaluated. The contribution of the study to the literature is that at the stage of developing a new product idea, companies that have a high level of knowledge about consumers and consumer groups will be able to develop products that perform at a higher level when they gain more information.